Remains of a Triratha single-shrine temple - Temples of India Project Team (Jio Institute, 2024)
The remains of a triratha (three ratha or vertical projections on each side) single-shrine temple to the southwest of the Mandaleshwar Mahadev Temple. The ruined temple consists of only a garbhagriha (sanctum sanctorum) and a mandapa (pillared hall) in its plan. Only the plinth of the temple ruins has survived. The temple has a vedibandha (basal mouldings) consisting of mouldings like khura, kani, and kumbha.